Financial integration and wage inequality: Evidence from European countries - Jinyeong Yun (Philipps-University Marburg, School of Business and Economics, 2024)
In this paper, I study the impact of financial integration on between-firm wage inequality using an unbalanced panel for 20 European countries over the period 1999-2021. With the impulse response functions estimated using local projections, I find that financial integration, as measured by the sum of external assets and liabilities, is associated with increased wage inequality within industries. These effects are more pronounced in the mid-term rather than in the short-term. The direction of financial integration, i.e., whether it involves an increase in external assets or liabilities, also matters: inward finan- cial integration significantly increases wage inequality, while outward financial integration does not. I also provide empirical evidence on the channel of distributional effects of financial integration. The financial integration shocks widen the capital intensity (the capital-to-labor ratio) gap within industries, which in turn widens the labor productivity gap. Through this channel, financial integration may affect between-firm wage inequality. Furthermore, the impact of financial integration on wage inequality depends on the external financial dependence of individual industries, while the moderating effect of financial development in each country is less definitive.
Keywords: D63; F36; F38; J31; 330; Financial integration; wage inequality; local projections